Білковий обмін фазанів за використання у складі комбікормів біомаси вермикультури - Гейсун, А. А.; Geysun, A. A.; Степченко, Лілія Михайлівна; Stepchenko, L.; Stepchenko, L. M. (Дніпровський ДАЕУ, 2018)
Важливе значення у забезпеченні біологічних потреб організму птиці мають високоякісні корми з достатнім умістом повноцінного білка. Одним зі шляхів забезпечення птиці природним органічним білком є використання як кормової добавки біомаси червоного каліфорнійського черв’яка. Виявлений вплив кормової добавки вермикультури у складі комбікормів на стан білкового обміну фазанят. На першому тижні життя фазанятам дослідної групи додавали 1,5% кормової добавки вермикультури від основного комбікорму, на другому тижні – 2,5%. Застосування кормової добавки вермикультури до комбікормів фазанят сприяє росту маси тіла птиці, що свідчить про активацію білкового обміну в організмі. У дослідних групах фазанят спостерігали зростання середньої маси тіла на 11,9% порівняно з контрольною групою. Згодування кормової добавки вермикультури обумовлює накопичення загального білка в плазмі крові фазанят 28- та 35-добового віку в середньому на 9,0% та 9,4% відповідно щодо показника крові птиці контрольної групи. У ці вікові періоди кількість альбуміну в крові дослідних фазанят зростала відповідно на 10,6% та 9,4% відносно контролю, що свідчить про активацію білоксинтезувальної функції печінки. Вміст глобулінів у крові дослідних фазанят протягом вікових періодів 14, 28 та 35 діб не змінювався. У крові птиці дослідної групи 35-добового віку на 21,9% зростав уміст сечової кислоти. За умов згодовування кормової добавки вермикультури вміст креатиніну в крові фазанят 28- та 35-добового віку зріс відповідно на 16,3% та 19,8% до цього показника у птиці контрольної групи. За умови годування фазанів кормовою добавкою вермикультури вміст загального білка крові позитивно корелює з масою птиці, коефіцієнт кореляції становить r = 0,95 (Р < 0,001). Застосування кормової добавки вермикультури, отриманої з біомаси червоних каліфорнійських черв’яків, вирощених на поживному субстраті з умістом біологічно активної добавки, у складі комбікормів, сприяє активації процесів білкового обміну та підвищенню продуктивності фазанят. High-quality feeds with sufficient content of full protein are of great importance in fulfilling the biological needs of the bird organism. One way to supply poultry with natural organic protein is the use of a red Californian worm as a feed supplement for biomass. The aim of the research was to identify the effect of vermiculture feed supplement in the combined feed biomass on the state of protein metabolism of pheasants. In the first week of life, pheasants of the experimental group were added 1.5% of vermiculture feed supplement to the main feed biomass, and during the second week – 2.5%. Adding vermiculture feed supplement to the fodder increases the body weight growth of the bird, indicating the activation of protein metabolism in the body of animals. In the experimental group, pheasants were observed to have an average weight increase of 11.9% compared to the control group. The addition of vermiculture feed supplement causes the accumulation of total protein in the blood plasma of 28- and 35-day-old pheasants per 9.0% and 9.4% on average respectively, comparing to the blood index of the control group. It has been found out that during these age periods the amount of albumin in the blood of experimental pheasants increases by 10,6 and 9,4% respectively, compared to the control group, indicating the activation of the liver protein synthesizing function. The content of globulins in the blood of experimental pheasants at the age of 14, 28 and 35 days did not change. It has been proved that in the blood of birds of the experimental group of 35-day-old age urinary acid content increases by 21,9% compared to the control group. It was also established that adding feed vermiculture supplement increases the content of creatinine in the blood of birds of the 28th and 35th day of age by 16,3 and 19,8%, respectively, compared to same indices of the control group. Adding feed vermiculture supplement positively correlated the content of total protein with poultry weight, with the correlation coefficient r = 0.95 (Р < 0,001). The use of vermiculture feed supplement derived from the biomass of red Californian worms grown on a nutrient substrate containing the biologically active additive Нumilid leads to the activation of protein metabolism and increased the productivity of pheasants. A promising area of research is the study of the effects of vermiculture feed supplement, which was obtained from the biomass of red Californian worms grown on a substrate containing on qualitative parameters of poultry meat.
The Protein Metabolism in Pheasants when Using Vermiculture in Combined Feed Biomass
Степченко Лілія Михайлівна https://orcid.org/0000-0001-8509-7048
Keywords: кров; blood; червоний каліфорнійський черв’як; red Californian worm; загальний білок; total protein; птиця; poultry; альбуміни; albumin; глобуліни; globulin